Cloud Computing adoption and implementation in University libraries in Africa: an overview (2015)
This paper makes an exploit into how cloud computing can change the computational resource utilization and value in the African University Libraries (A ULs) terrain. It takes a look at the economics of providing computational resources through cloud computing web services providers like Amazon, using the concepts of utility services providers like, in the case of electricity consumption, pre-paid meter which is operated on ‘pay per use' basis. This approach is cost effective in terms of implementation in that since the server resides in the cloud, it follows that the required space for storing data will be used at a particular point in time, thereby the unused server space can be allocated to other customers using the same cloud service on request instead of allowing it to waste away. Personnel cost, with regards to technical staff will be reduced to the barest minimum since the issue of baby-sitting server must have been eliminated at the point of requesting for cloud services. Given limited available financial support at the disposal of AULs, server space economy, disaster recovery>, prudent infrastructural utilization, seamless resource sharing, a robust, sustainable and efficient backup plans, among others, will be the resultant benefits of cloud computing adoption and implementation to A ULs for efficient, timely and effective sendee delivery. All these are exhaustively discussed in this paper. A model of adoption and implementation as well as a review of what same will translate to within the A UL systems are also presented. This article is an overview of the adoption and implementation of cloud computing services in AULs with an associated model which can be used as a benchmark for implementation strategies within the AUL systems. An exhaustive practical implementation plan is strongly recommended for future research which will incorporate result analysis as well as exhaustive discussion of findings